2013
DOI: 10.1681/asn.2013010060
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deletion of Cell Division Autoantigen 1 Retards Diabetes-Associated Renal Injury

Abstract: Cell division autoantigen 1 (CDA1) enhances TGF-b signaling in renal and vascular cells, and renal expression of CDA1 is elevated in animal models of diabetes. In this study, we investigated the genetic deletion of Tspyl2, the gene encoding CDA1, in C57BL6 and ApoE knockout mice. The increased renal expression of TGF-b1, TGF-b type I and II receptors, and phosphorylated Smad3 associated with diabetes in wild-type mice was attenuated in diabetic CDA1 knockout mice. Notably, CDA1 deletion significantly reduced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 34 publications
2
47
0
Order By: Relevance
“…We used ApoE 2/2 mice because streptozotocin-induced diabetes in ApoE 2/2 mice is a well characterized model of advanced renal injury with prominent ECM accumulation. 28,29 Importantly, we translated these findings into a potential clinical therapy by showing that Nox inhibition in diabetic ApoE 2/2 mice using a pharmacologic strategy resulted in a similar degree of renoprotection to that observed with deletion of Nox4.…”
Section: Discussionmentioning
confidence: 99%
“…We used ApoE 2/2 mice because streptozotocin-induced diabetes in ApoE 2/2 mice is a well characterized model of advanced renal injury with prominent ECM accumulation. 28,29 Importantly, we translated these findings into a potential clinical therapy by showing that Nox inhibition in diabetic ApoE 2/2 mice using a pharmacologic strategy resulted in a similar degree of renoprotection to that observed with deletion of Nox4.…”
Section: Discussionmentioning
confidence: 99%
“…55 Interestingly, targeted deletion of Tspyl2 did not affect other features, such as hyperglycaemia, renal hypertrophy, or hyperfiltration, in these diabetic mice. 55 Although additional studies are required to evaluate the potential effect of CDA1 inhibition on sustained protein-uria and progressive fibrosis, its actions in reducing TGF-β-mediated matrix accumulation provide support for CDA1 as a potential therapeutic target to slow the progression of CKD.…”
Section: The Role Of Tgf-β In Renal Fibrosismentioning
confidence: 80%
“…In a separate study, the role of TSPY-like protein 2 in regulating TGF-β signalling was demonstrated. 55 In diabetic Tspyl2 –/– mice there was reduced renal accumulation of extra cellular matrix proteins and decreased glomerular and tubulointerstitial injury were observed, along with decreased gene expression of TGF-β and TGF-β type I receptor, and decreased levels of phosphorylated Smad3. 55 Interestingly, targeted deletion of Tspyl2 did not affect other features, such as hyperglycaemia, renal hypertrophy, or hyperfiltration, in these diabetic mice.…”
Section: The Role Of Tgf-β In Renal Fibrosismentioning
confidence: 96%
See 2 more Smart Citations